Preface - Blair, Sampson Lee (2020)
A common sentiment shared in many cultures around the globe is that parenting is "the hardest job you will ever love." For many, this association is related to the many long, sleepless nights spent attending to the needs of infants. During this time, feeding, bathing, and the seemingly endless diaper changes lead many to assume that their decision to have a child was perhaps a bit premature, as they had not accounted for the tremendous physical demands that childrearing places upon mothers and fathers. However, while the needs of children will change as they age, the truly complex nature of parenthood begins to reveal itself. Around their second birthday, children begin to speak, thus opening up a completely new set of needs, as parents now have to engage their child in conversation. At this point, children can now express not only their physical needs, but also their wide array of emotional and cognitive needs to parents. Later, as children grow and are able to leave the home for school, their needs become ever more complicated, as interactions with peers and the larger society outside the family begin to influence their development. The middle childhood years offer little relief for parents, nor do their often turbulent adolescent years. Simply, there is considerable recognition that parenting is, indeed, a most demanding role for mothers and fathers.